The importance of didactic-pedagogic practices and resources for teaching geography - Diniz, Ana Cláudia Araújo; Fortes, Mircia Ribeiro (Revista Ensino de Geografia (Recife), 2019)
Currently, in contrast to what is specified in Brazil's educational legislation, the focus of education generally remains on training for the labor market, contrary to the perspective of integral education determined in the Federal Constitution and in the Law of Guidelines and Bases of National Education, through a decontextualized teaching regarding the different realities of the students in the national context. It is noteworthy that in this teaching format, old-fashioned methods and resources prevail that distancing students from school knowledge and environment, making the teaching-learning process extremely difficult. In this perspective, it isntended to show, through bibliographical research and the results of pedagogicalpractices of supervised internship, the possibilities of promising practices and methodologies to the teaching of geography, which can be considered as facilitators in the teaching-learning process. It is noteworthy that the use of languages such as movies, games, literary works, cartoons, comics, songs, as well as field lessons (technical visits), have educational potential of contextualization and approximation of students to knowledge related to the same Geography discipline or, often superior to the textbook